Survival Prediction of Patients Treated With Immune Checkpoint Inhibitors via KRAS/TP53/EGFR-Single Gene Mutation - Shui Liu; Shuai Geng; Ning Shi; Lili Zhang; Wenxin Xue; Yiwen Li; Kai Jiang (Frontiers Media S.A., 2022)
Background: Immune checkpoint inhibitors (ICIs) have become an effective treatment option for cancer. KRAS, EGFR and TP53 are common mutated oncogenes in cancer whose single gene status may predict the therapeutic effect of clinical ICIs. In this efficacy evaluation, we aimed to clarify whether the single gene mutation status of KRAS, EGFR or TP53 affects the survival benefits of ICIs in cancer patients.Methods: We used PubMed, Cochrane Library, web of science, and clinical trials Gov database to retrieve qualified documents, the time was up to January 2022. Hazard ratios (HRS) and 95% confidence intervals (CIs) were used to determine the single gene mutation status and no progression of KRAS, EGFR or TP53.Results: A total of 19 studies included 7029 cancer patients treated with ICIs. The results showed that KRAS, EGFR or TP53 single gene mutation could significantly improve PFS and OS in patients receiving ICIs, but the degree of improvement was different. The risk of prolongation of PFS (HR = 1.48, 95% CI = 1.19-1.85, p = 0.0004) and OS (HR = 1.68, 95% CI = 1.36-2.07, p < 0.00001) caused by TP53 single gene mutation was relatively high, the risk ratio of prolongation of PFS (HR = 1.38, 95% CI = 1.21-1.57, p < 0.00001) and OS (HR = 1.56, 95% CI = 1.20-2.04, p = 0.001) caused by EGFR single gene mutation was the second, the risk ratio of prolongation of PFS (HR = 1.33, 95% CI = 1.12-1.57, p = 0.001) and OS (HR = 1.39, 95% CI = 1.18-1.63, p < 0.00001) caused by KRAS single gene mutation was relatively low, and the results were significantly different.Conclusion: In cancer patients, KRAS, EGFR or TP53 single gene status is correlated with the benefits of immunotherapy PFS and OS, which suggests that gene sequencing should be carried out in time in the process of clinical treatment to determine the gene mutation of patients and better predict the clinical treatment effect of ICIs.